2007
DOI: 10.1007/s10661-007-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heavy metal pollution on enzyme activities and basal soil respiration of roadside soils

Abstract: In this study, soil samples (0-5 cm depth) were taken from ten different roadside fields of intensive traffic regions of Van-Turkey in order to determine the effects of heavy metal pollution on enzymes and microbial activities of soils. Basal soil respiration (BSR), arylsulphatase (ASA), alkaline phosphatase (APA) and urease (UA) enzyme activities, and heavy metal contents (Pb, Cr, Ni, Cd, Fe, Mn, Cu and Zn) of soils significantly changed with 5, 25 and 45 m from the roadside of soil sampling positions. BSR, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
39
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 30 publications
7
39
0
2
Order By: Relevance
“…The intensity of the hydrolysis of sulfate esters is negatively correlated with the contents of lead and copper in the soil, and to a smaller extent with the contents of zinc, nickel, and cadmium [35]. Nevertheless, an increase in contamination of the soil environment with zinc and cadmium may adversely affect arylsulfatase activity.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The intensity of the hydrolysis of sulfate esters is negatively correlated with the contents of lead and copper in the soil, and to a smaller extent with the contents of zinc, nickel, and cadmium [35]. Nevertheless, an increase in contamination of the soil environment with zinc and cadmium may adversely affect arylsulfatase activity.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Firstly, improvements in soil physicochemical conditions, especially OM, may have inactivated the impacts of metals. According to Gülser and Erdogan (2008), OM-metal complexes occur in OM and soil solutions and would prevent the metals from interacting directly with the active sites of enzymes. Kizilkaya and Bayrakli (2005) found that sludge application increased available metal (Cu, Ni, Pb and Zn) contents in the soils.…”
Section: Resultsmentioning
confidence: 99%
“…Even though metals like Zn, Cu and Mn act as cofactor in several enzyme activities and that Fe is directly involved with haemoglobin formation in the blood tissues, their presence in excessive concentration might be toxic to the fish (Zyadah and Abdel-Bakey 2000;Ikem et al 2003). Pb is also a toxic element and has no known biological function and shows its negative health effect on aquatic biota and humans (Shahtaheri et al 2007;Gulser and Erdogan 2008). Chromium is considered as essential trace elements.…”
Section: Resultsmentioning
confidence: 99%